D‐dimer level for ruling out peripherally inserted central catheter‐associated upper extremity deep vein thrombosis and superficial vein thrombosis - Wanli Liu; Lianxiang He; Wenjing Zeng; Liqing Yue; Jie Wei; Shuangshuang Zeng; Xiang Wang; Zhicheng Gong (Wiley, 2022)
Abstract Aims To examine the effectiveness of D‐dimer values to be used as an independent diagnostic marker for excluding peripherally inserted central catheter‐associated upper extremity deep vein thrombosis and superficial vein thrombosis. Design This was a retrospective case-cohort study. Methods Records were reviewed for 281 patients who underwent peripherally inserted central catheter insertion between 1 October 2017 and 1 October 2019. According to the modified Wells score after peripherally inserted central catheter insertion, the patients who had low vein thrombosis risk underwent a D‐dimer test and colour Doppler ultrasound. Results Among 281 patients, 180 patients (64%, 95% CI: 58.2%-69.4%) had negative D‐dimer results and 39 of 180 patients had vein thrombosis despite having a negative D‐dimer result, resulting in a failure rate of 21.7% (95% CI: 16.3%-28.3%). The negative predictive value of peripherally inserted central catheter‐associated vein thrombosis in the cancer group (80.0%, 95% CI: 73.2%-85.4%) was higher than that of the non‐cancer group (60.0%, 95% CI: 35.7%-80.2%). The negative predictive value of peripherally inserted central catheter‐associated deep venous thrombosis (84.9%, 95% CI: 78.7%-89.6%) was lower than that of the PICC‐associated superficial venous thrombosis (91.0%, 95% CI: 85.4%-94.6%). Conclusion The D‐dimer levels maybe should not be used as a diagnostic index to rule out peripherally inserted central catheter‐associated upper extremity vein thrombosis.